EVALUATION OF POLYMORPHIC VARIANTS OF GENES OF SOMATOTROPIN CASCADE AS GENETIC MARKERS OF MEAT PRODUCTIVITY IN DOMESTIC CATTLE BREED - A. Taipova, A.; Beishova, I.; Alikhanov, K.; Belaya, E. (Ғылым және білім №1, 2020)
It is known that growth hormone (GH-somatotropin) is the most important growth regulator in mammals. Synthesis of somatotropin and the realization of its physiological effects is a chain of successive interactions of the protein receptor (self-tropic cascade). The key links of this chain are the pituitary transcription factor-1 (bPit- 1), triggering the expression of the genes of somatotropin and prolactin, prolactin and growth hormone, regulating lactation, the growth hormone receptor (bGHR), which transmits the somatotropin humoral signal to target cells. Thus, based on the researches performed, the following data is stated below. On the first hand, specified allele frequencies for all the polymorphisms in question are comparable with the other authors’ data; rare allele of other breed representatives are also rare according to the results of our research. The research works were performed within the frameworks of the scientific project of the Ministry of Education and Science of the Republic of Kazakhstan.Известно, что гормон роста (GH – соматотропин) является важнейшим регулятором роста у млекопитающих. Синтез соматотропина и реализация его физиологических эффектов представляет собой цепь последовательных взаимодействий белок – рецептор (соматотропиновый каскад). Ключевыми звеньями этой цепи являются гипофизарный фактор транскрипции-1 (bPit-1), запускающий экспрессию генов соматотропина и пролактина, пролактин и гормон роста, регулирующие лактацию, рецептор гормона роста (bGHR), передающий гуморальный сигнал соматотропина к клеткам-мишеням.
Keywords: журнал кксон; рк; научный журнал; периодическое издание; отечественное издание; ветеринария; соматотропин; рецептор гормона роста; лактация; somatropine cascade; cattle; gene; polymorphism